Hyperactivity of Hypothalamic-Pituitary-Adrenal Axis Due to Dysfunction of the Hypothalamic Glucocorticoid Receptor in Sigma-1 Receptor Knockout Mice - Di, Tingting; Zhang, Suyun; Hong, Juan; Zhang, Tingting; Chen, Ling (Frontiers in Molecular Neuroscience, 2017)
Sigma-1 receptor knockout (σ1R-KO) mice exhibit a depressive-like phenotype. Because σ1R is highly expressed in the neuronal cells of hypothalamic paraventricular nuclei (PVN), this study investigated the influence of σ1R deficiency on the regulation of the hypothalamic-pituitary-adrenocortical (HPA) axis. Here, we show that the levels of basal serum corticosterone (CORT), adrenocorticotropic hormone (ACTH) and corticotrophin releasing factor (CRF) as well as the level of CRF mRNA in PVN did not significantly differ between adult male σ1R-KO mice and wild-type (WT) mice. Acute mild restraint stress (AMRS) induced a higher and more sustainable increase in activity of HPA axis and CRF expression in σ1R-KO mice. Percentage of dexamethasone (Dex)-induced reduction in level of CORT was markedly attenuated in σ1R-/- mice. The levels of glucocorticoid receptor (GR) and PKC phosphorylation were reduced in the PVN of σ1R-KO mice and σ1R antagonist NE100-treated WT mice. The exposure to AMRS in σ1R-KO mice induced a stronger phosphorylation of cAMP-response element binding protein (CREB) in PVN than that in WT mice. Intracerebroventricular (i.c.v.) injection of PKC activator PMA for 3 days in σ1R-KO mice not only recovered the GR phosphorylation and the percentage of Dex-reduced CORT but also corrected the AMRS-induced hyperactivity of HPA axis and enhancement of CRF mRNA and CREB phosphorylation. Furthermore, the injection (i.c.v.) of PMA in σ1R-KO mice corrected the prolongation of immobility time in forced swim test and tail suspension test. These results indicate that σ1R deficiency causes down-regulation of GR by reducing PKC phosphorylation, which attenuates GR-mediated feedback inhibition of HPA axis and facilitates the stress response of HPA axis leading to the production of depressive-like behaviors.